Nursing preoperative checklist for safe surgery - Ariel P Ramos; Roberto de Anton; Ethel Guidi; Stella M Delor; Liliana Lupica; Viviana B Fraiz; Dario Fidel; Sabrina Arena; Eduardo B Arribalzaga (Archives of Nursing Practice and Care - Peertechz Publications, 2019)
Background: Safety in the care of patients is a priority in the design of any health system, having direct implications on the quality of care. Assessment of nurses in hospital rooms allows to detect difficulties or problems in preoperative which can endanger the patient's life or the expected result of the surgery. Is there where you must generate protocols that ensure safety for patients, decreasing the maximum errors and comply with the premise made by WHO in 2008: "Safe surgery saves lives". Objective: The pre-operative checklist of nursing to reduce errors in the admission of patients to operating rooms was applied.